REJUVENATION OF RELIGION IN BUILDING DIALOGUE AND HARM IN NTT - Maku, Hendrikus; Edu, Ambros Leonangung; Paulus Tolo (CV. AFDIFAL MAJU BERKAH, 2023)
Rejuvenation of religion is one of the right steps to address public unrest related to the presence of transnational ideology in East Nusa Tenggara (NTT). The Human Fraternity document signed by Pope Francis and Sheikh of Al-Azhar, Ahmad Al-Tayyeb, very cleverly compiled constructive ideas for the purpose of religious rejuvenation. A very fundamental point in the spirit of Human Fraternity is interpreting religion not as a wall that separates followers of religion, but rather as a bridge that leads followers of religions to meet and make peace with followers of other religions. The straight path to the bridge of peace is dialogue that can be implemented in many forms and ways. With a dialogical spirit nourished by the idea of religious rejuvenation inspired by the document, we can certainly paralyze the radical understanding or transnational ideology that is always counterproductive to NTT's public dreams, to build the future of religious harmony in the foundation of Pancasila (National Ideology) and Multiculturalism in order to create a prosperous NTT community